Neglected serial correlation tests in UCARIMA models - Gabriele Fiorentini; Enrique Sentana (SERIEs - Journal of the Spanish Economic Association, 2016)
We derive computationally simple and intuitive score tests of neglected serial correlation in unobserved component univariate models using frequency domain techniques. In some common situations in which the alternative model information matrix is singular under the null, we derive one-sided extremum tests, which are asymptotically equivalent to likelihood ratio tests, and explain howto compute reliable Wald tests. We also explicitly relate the incidence of those problems to the model identification conditions and compare our tests with tests based on the reduced form prediction errors. Our Monte Carlo exercises assess the finite sample reliability and power of our proposed tests.
Keywords: C22; C52; C12; 330; Extremum tests; Kalman filter; LM tests; Singular information matrix; Spectral maximum likelihood; Wiener-Kolmogorov filter